Water governance as an instrument of democratization: reflections on the shared management of water resources in Brazil - Matos , Fernanda; Dias, Reinaldo (Seven Editora, 2023)
Recent changes in society continue to call into question the ability of core states to manage increasingly complex development issues on their own. Water governance remains a critical issue, as it involves determining the roles and responsibilities of different interests – public, civil, and private – in the management and development of water resources, analyzing the balance of power and actions at different levels of authority. Water governance must be readapted and translated specifically into political systems, laws, regulations, institutions, financial mechanisms, civil society development, and consumer rights. It must go beyond the traditional public sector and market-oriented sectors of governance, seeking coordinated schemes in which new, more dynamic relationships emerge between different participants and stakeholders (Sandoval, 2007). DOI: https://doi.org/10.56238/devopinterscie-047